A new species and first stage associations in Crinitella (Ephemeroptera: Ephemerellidae: Ephemerellinae) - Jacobus, Luke M.; Mccafferty, W. P.; Sites, Robert W. (Zootaxa, 2007)
The alates of Crinitella coheri (Allen and Edmunds) are described for the first time, and morphological variability of the species is discussed. Male adults have penes with dorsal projections at the base of the gonopores and forceps with a relatively straight lateral profile. Crinitella coheri female alates and associated eggs have been misidentified as those of a Hyrtanella species. Crinitella coheri is reported from Vietnam for the first time. We describe C. lacuna, new species, based on male and female subimagoes and larvae, and the species is included in Crinitella on the basis of genitalia morphology. Alates of C. lacuna are distinguished from C. coheri by the presence of a prominent dorsal longitudinal stripe, and larvae are distinguished by having paired median spines on abdominal terga, mouthparts that are not greatly reduced, and gills 3 that are relatively larger than those of C. coheri. Crinitella lacuna is reported from India, Thailand and Vietnam. The structures of Crinitella and Hyrtanella gill cavities are different and do not represent a synapomorphy for the two genera.